2016
DOI: 10.1161/atvbaha.115.306396
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin Relates to Carotid Intima-Media Thickness in Offspring of Fathers With Higher Serum Ferritin Levels

Abstract: Objective-Body iron status has been linked to atherosclerosis in adults. The purposes of our study were to determine (1) the association between circulating ferritin levels and carotid intima-media thickness (cIMT) in a cohort of apparently healthy children and (2) the association between cIMT and parental ferritin levels. Approach and Results-Circulating ferritin levels (microparticle enzyme immunoassay), metabolic parameters, and cIMT (ultrasonography) were analyzed cross-sectionally in a cohort of 692 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A recent meta-analysis shows 8 hat 1 m/s increase in PWV is associated with a 15% risk increase of CV mortality in about 16,000 individuals followed up for a mean of 8 years [17]. Although there is some evidence of an independent association between hyperferritinemia and arterial stiffness in disparate populations [18][19][20][21], data in hypertensive patients are few.…”
mentioning
confidence: 99%
“…A recent meta-analysis shows 8 hat 1 m/s increase in PWV is associated with a 15% risk increase of CV mortality in about 16,000 individuals followed up for a mean of 8 years [17]. Although there is some evidence of an independent association between hyperferritinemia and arterial stiffness in disparate populations [18][19][20][21], data in hypertensive patients are few.…”
mentioning
confidence: 99%
“…While most of the clinical studies to assess the validity of the iron hypothesis have been performed in patients with CVD or altered iron status, a nuanced understanding of how small fluctuations of iron parameters within the physiological limits predispose to atherosclerosis in the healthy population is still lacking. A recent human population study reported for the first time a correlation between circulating ferritin levels and carotid-intima media thickness in a large healthy cohort of 692 children ( 171 ). Importantly, a J-shaped association of systemic iron status and cardiovascular mortality has been recently described in CAD patients ( 87 , 163 ).…”
Section: Novel Evidence On the Vasculotoxic And Atherogenic Impact Of Ironmentioning
confidence: 99%
“… 21 In another study performed on obese adults with non-alcoholic fatty liver disease, there was no relationship between ferritin levels and IMT. 22 In children, serum ferritin levels were associated with IMT in healthy subjects 23 and children with sickle cell disease, 24 but not those with thalassemia. 25 26 We previously reported increased IMT in obese children.…”
Section: Introductionmentioning
confidence: 98%